2018
DOI: 10.1136/gutjnl-2018-317111
|View full text |Cite
|
Sign up to set email alerts
|

An Asian consensus on standards of diagnostic upper endoscopy for neoplasia

Abstract: BackgroundThis is a consensus developed by a group of expert endoscopists aiming to standardise the preparation, process and endoscopic procedural steps for diagnosis of early upper gastrointestinal (GI) cancers.MethodThe Delphi method was used to develop consensus statements through identification of clinical questions on diagnostic endoscopy. Three consensus meetings were conducted to consolidate the statements and voting. We conducted a systematic literature search on evidence for each statement. The statem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
108
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 108 publications
1
108
0
2
Order By: Relevance
“…We expect that this consensus will contribute to standardization of the quality of diagnostic colonoscopy in Asia and, hopefully, in other parts of the world. Future perspective of our group is to develop consensus statements on endoscopic treatment of GI neoplasia …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We expect that this consensus will contribute to standardization of the quality of diagnostic colonoscopy in Asia and, hopefully, in other parts of the world. Future perspective of our group is to develop consensus statements on endoscopic treatment of GI neoplasia …”
Section: Discussionmentioning
confidence: 99%
“…Future perspective of our group is to develop consensus statements on endoscopic treatment of GI neoplasia. 168…”
Section: Discussionmentioning
confidence: 99%
“…Though the overall survival of GC patients to some extent has improved due to the application of early detection technology and radical surgery, most early‐stage gastric cancer (EGC) patients have no characteristic manifestations, and many patients are still diagnosed at the advanced stages and miss the best chance to therapy . Nowadays, upper gastrointestinal (GI) endoscopy followed by pathologic examination remains the golden standard for the diagnosis of GC . However, upper GI endoscopy is not a routine medical examination in most countries, and making a gastroscopy inspection is an invasive technique that will sometimes make patients uncomfortable .…”
Section: Introductionmentioning
confidence: 99%
“…2 Nowadays, upper gastrointestinal (GI) endoscopy followed by pathologic examination remains the golden standard for the diagnosis of GC. 3 However, upper GI endoscopy is not a routine medical examination in most countries, and making a gastroscopy inspection is an invasive technique that will sometimes make patients uncomfortable. 4 On a global scale, a recent study showed that the 5-year survival rate of stage I patients can be more than 90%, while that of the stage IV patients who already show distant metastases is only approximately 18%.…”
Section: Introductionmentioning
confidence: 99%
“…Consensus guidelines of standards for diagnostic upper and lower GI endoscopy have been published, and all endoscopists should be mindful of the requirements for a quality examination. (8,9) GI neoplasia, including early cancer with no or minimal risk of metastases, should undergo curative endoscopic resection. This curative treatment option is minimally invasive and organ preserving.…”
mentioning
confidence: 99%